Clinical pharmacist interventions in the transition of care in a mental health hospital: case reports focused on the medication reconciliation process - Stuhec, Matej; Batinic, Borjanka (Frontiers in Psychiatry, 2023)
The transition of care represents a key point in the hospital admission and discharge process. A comprehensive transition could lead to less medication-related problems. The hospital clinical pharmacist could help in the transition of care process with the comprehensive medication reconciliation process, which has been poorly described in mental health hospitals. This paper presents two clinical cases in which hospital clinical pharmacists identified omitted medications and other medication-related issues, including medication errors, during the transition of care in a mental health hospital. These positive experiences may encourage other countries to establish similar collaborations with hospital clinical pharmacists in mental health hospitals.